Comparative evaluation of the effects of bisphenol derivatives on oxidative stress parameters in HepG2 cells. (4th March 2023) - Ozyurt, Busra; Ozkemahli, Gizem; Yirun, Anil; Ozyurt, Aylin Balci; Bacanli, Merve; Basaran, Nursen; Kocer-Gumusel, Belma; Erkekoglu, Pinar
Abstract: Bisphenol A (BPA) BPA is an endocrine-disrupting chemical that has a wide range of uses. Exposure to BPA can be by oral, inhalation, and parenteral routes. Although its use in several products is limited, there is still concern on its adverse health effects, particularly for susceptible populations like children. Alternative bisphenols, such as bisphenol S (BPS) and bisphenol F (BPF), are now being used instead of BPA, although there is little information on the toxicity of these bisphenols. BPF is used as a plasticizer in the production of several industrial materials as well as in the coating of drinks and food cans. BPS is used in curing fast-drying epoxy glues, as a corrosion inhibitor and as a reactant in polymer reactions. In this study, the possible toxic effects of BPA, BPS, and BPF in HepG2 cells were evaluated comparatively. For this purpose, their effects on cytotoxicity, production of intracellular reactive oxygen species (ROS), oxidant/antioxidant parameters, and DNA damage have been examined. The cytotoxicity potentials of different bisphenols were found to be as BPS > BPF > BPA. All bisphenol derivatives caused increases in intracellular ROS production. We observed that all bisphenol derivatives cause an imbalance in some oxidant/antioxidant parameters. Bisphenols also caused significant DNA damage in order of BPF > BPA > BPS. We can suggest that both of the bisphenol derivatives used as alternatives to BPA also showed similar toxicities and may not be considered as safe alternatives. Mechanistic studies are needed to elucidate this issue.